Conduct an advanced numerical simulation investigation on the rutting performance of coal liquefaction residue asphalt mixture - Wang, Zhe; Wang, Zhen; Sha, Chuan; Guo, Shuangfeng; Zheng, Wenhua; Cao, Hongbo; Shan, Xiaowei; Cao, Guoqing; Ji, Jie; Li, Pengfei (Frontiers in Materials, 2025)
Coal liquefaction residue (CLR), a byproduct of coal-to-liquid technology known to adversely affect the ecological environment and human health, was investigated in this study for its influence on the rutting resistance of asphalt mixtures. The research employed the discrete element method in PFC2D to develop a rutting model, analyzing mixture behavior under varying temperatures and loads. CLR was used to replace fine aggregate volumetrically, with particular focus on particles ranging from 0 to 4.75 mm. Macroscopic rutting behavior was evaluated by examining fine particle displacement and force chain distribution. Results revealed that rutting development follows a power-function growth pattern, divided into three stages: 0–10 minutes, 10–20 minutes, and 20–60 minutes, with the initial 20 minutes being critical for rut formation. Particles exhibited strong self-organization adaptability, reducing stress concentration at rut initiation. During rutting evolution, particles sized 0.6–2.36 mm contributed significantly to deformation, while smaller particles (1.18–2.36 mm) were more prone to passive displacement due to compression and collision with larger particles (2.36–4.75 mm). In asphalt mortar with higher adhesive strength, however, the 0.6–1.18 mm particles were more extensively coated by larger ones, resulting in reduced displacement compared to the 1.18–2.36 mm fraction. The 2.36–4.75 mm particles served as a macroscopic skeleton, bearing and transmitting contact forces. Numerical simulations confirmed the rationality of replacing the 1.18–2.36 mm and 2.36–4.75 mm particles with indirect CLR of single particle sizes, and the 0.6–1.18 mm and 1.18–2.36 mm particles with direct CLR of single particle sizes. It was concluded that direct CLR significantly enhances the high-temperature performance of asphalt mixtures compared to indirect CLR, which aligns with macroscopic rutting test outcomes.